Synthesis of isoquinolone via rhodium(III)-catalyzed C-H activation with 1, 4, 2-dioxazol-5-ones as oxidizing directing group. Issue 23 (7th June 2019) - Zhu, Huajian; Zhuang, Rangxiao; Zheng, Wenya; Fu, Liping; Zhao, Yuanke; Tu, Luping; Chai, Yitao; Zeng, Linghui; Zhang, Chong; Zhang, Jiankang
Abstract: An efficient rhodium-catalyzed direct C-H activation for the synthesis of isoquinolone with 1, 4, 2-dioxazol-5-ones as oxidizing directing groups have been developed, which featured mild reaction conditions, short reaction time and satisfactory yield. Graphical abstract: An efficient approach to isoquinolone have been developed, which featured in completing expeditiously under mild conditions with satisfactory yield.Image 1